PENGARUH METODE DRILL TO DRILL DALAM MENINGKATKAN KEMAMPUAN MENULIS STRUKTUR TEKS BERITA DI KELAS VIII SMP IT AN-NAFIS TELUK MENGKUDU TAHUN PEMBELAJARAN 2025-2026 - Sari, Ayu Permata (Jurnal Lazuardi, 2025)
This research aims to determine the effect of the drill to drill method to improve the writing skills of class VIII SMP IT An-Nafis Teluk Mengkudu students. The sample for this research was 19 students in class VIII in the control class and 20 students in the experimental class in class VIII of SMP IT An-Nafis Teluk Mengkudu, which was determined using random sampling. The method used in this research is an experiment with a Two-Group-Pre-test and Post-test research design. From data analysis, the average score (pre-test) of the control class was 61.35789 and (post-test) of the control class was 68.20526, while the average score (pre-test) of the experimental class was 60.8 and (post-test) of the experimental class was 85.85. Before the hypothesis test was carried out, prerequisite analysis tests were carried out, namely the normality test and homogeneity test, the normality test results were L_count < L_tabel (0.15073 < 0.381) and the homogeneity test results were So Fcount < Ftable, namely 0.187 < 2.18. Based on the results of data analysis, it was found that the post-test data for the control class and experimental class were normally distributed and homogeneous. Thus, it can be concluded that because t count > t table, namely 2,292 > 1,687, the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. This proves that there is a significant influence of the drill to drill method in improving students' writing skills.